PENGARUH LEVERAGE, INTENSITAS ASET TETAP DAN KONEKSI POLITIK TERHADAP PENGHINDARAN PAJAK - Manihuruk, Keyko Artazenia; Yusralaini, Yusralaini; Hanif, Rheny Afriana (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2025)
This study aims to test and analyze the effect of leverage, fixed asset intensity and political connections on tax evasion in non-cyclical consumer sector companies listed on the Indonesia Stock Exchange (IDX-IC) during the 2021-2023 period. The research sample of 57 companies was selected using purposive sampling technique. The data analysis method applied is multiple linear regression with the help of the IBM SPSS Statistics 26 application. The results showed that leverage has no effect on tax avoidance, while fixed asset intensity has a negative effect on tax avoidance, and political connections have a positive effect on tax avoidance.